DISEMINASI INFORMASI DAN DETEKSI DINI GANGGUAN KOGNITIF TERKAIT HIPERTENSI PADA PENDUDUK DI DESA PULAU MARINGKIK, KABUPATEN LOMBOK TIMUR - Herpan Syafii Harahap; Yanna Indrayana; Yusra Pintaningrum; Bambang Priyanto; Arina Windri Rivarti; Dini Suryani; Nurhidayati Nurhidayati; Legis Ocktaviana Saputri; Fitriannisa Faradina Zubaidi; Muhammad Hilman Rizaldi; Anang Hermansyah; Restia Restia (Universitas Mataram, 2023)
Hypertension-related cognitive impairment has a wide spectrum, ranging from mild cognitive impairment to severe cognitive impairment in hypertensive individuals. Hypertension is currently also known as a risk factor for Alzheimer's dementia and vascular dementia. In its severe form, cognitively impaired individuals will have a high dependence on family members to carry out their daily activities. This community service event aims to increase the understanding of the residents of Maringkik Island Village regarding ​​the importance of prevention and early detection of hypertension-related cognitive impairment. This event was carried out in Pulau Maringkik Village, East Lombok Regency, which is a representative of a coastal area whose population generally has a high level of consumption of sodium salt. This community service activity is carried out in 3 forms of activities, including health education, screening of hypertension, and early detection of cognitive impairment in hypertensive participants. This health education event was attended by 53 participants. Of these, 29 participants (54.7%) were hypertensive. In early detection of cognitive dysfunction, of the 29 hypertensive participants, 19 of them (65.5%) were categorized as having impaired cognitive function. Thus, in this community service events, health education activity, screening of hypertension, and early detection of hypertension-related cognitive impairment are successfully done. The frequency of residents of Maringkik Island Village with hypertension and hypertension-related cognitive impairment is quite high. Promotive efforts to change high-sodium salt consumption habits need to be carried out on an ongoing basis with an educational strategy that is adjusted to the education level of the participants.